PERBANDINGAN METODE WIENER FILTER DAN TRIVARIATE SHRINKAGE UNTUK MEMPERBAIKI KUALITAS CITRA DIGITAL - Sinaga, Ribka Delima (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
The use of digital image plays an important role as a form of information due to the advantages possessed. Although rich in information, not all imagery has a good visual appearance. This can be caused by noise, color intensity that is too contrast or blurred. Noise itself is a disturbance caused by the deviation of digital data received by the image data receiving device, ranging from movement during shooting by optical devices such as cameras, the use of optical devices that are not focused, the lighting is short so as to reduce the number of photons captured by optical devices, or weather when shooting. Noise can be removed using filtering techniques. Low-quality image caused by noise requires improvement measures to improve image quality without reducing more image detail quality and produce images with fairly accurate information, noise can be reduced or eliminated by using filtering techniques